In Vitro Antibacterial Activity and Mode of Action of Piper betle Extracts against Soft Rot Disease-Causing Bacteria - Punyisa Charirak; Rapeepun Prajantasan; Kantapon Premprayoon; Nikom Srikacha; Khakhanang Ratananikom (Scientifica)
Soft rot disease affects a range of crops in the field and also during transit and storage, resulting in significant yield losses and negative economic impacts. This study evaluated the in vitro antibacterial activities and mode of action of Piper betle extracts against the soft rot disease-causing bacteria, Erwinia caratovora subsp. caratovora (ECC). Dried leaves of P. betle were extracted with water, ethanol, and hexane solvents and evaluated for their antibacterial activity. The results showed the highest antibacterial activity against ECC in the ethanol extract, followed by hexane and water extracts with minimum inhibitory concentration (MIC) 1.562, 6.25, and more than 12.50 mg/mL, respectively. The time-kill assay indicated a bactericidal mode of action. ECC growth was destroyed within 6 and 8 hours after treatment with the ethanol extract at 4-fold MIC and 2-fold MIC, respectively. The ethanol extract of P. betle showed promising activity against ECC, with the potential for further development as a novel alternative treatment to control phytobacteria.